Perkembangan Kognitif Masa Anak-Anak Awal - Fauziah Nasution; Rahmi Aulia; Innaya Rahmadhini Edith; Nurjannah Rangkuti; Bima Khoirur Rozzaq (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This journal discusses cognitive development during early childhood. The aim of writing the journal is to find out how cognitive development occurs during early childhood, the advantages of cognitive development during early childhood, as well as language abilities and other cognitive abilities. The method used is literature study, namely by searching for materials and references from books, journals and articles. The results show that the early childhood period is called preoperational, this period starts from the age of 2 to 7 years. Preoperational uses symbols, categorization, and numbers. Other cognitive abilities are life, death, bodily functions, space, weight, numbers, time, social impressions, beauty and cuteness.